2018
DOI: 10.1111/aos.14002
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal thickness following panretinal photocoagulation using a multispot semi‐automated pattern‐scanning laser to treat ischaemic diabetic retinopathy: Treatment in one session compared with four monthly sessions

Abstract: PurposeTo compare central retinal thickness (CRT) after panretinal photocoagulation (PRP) with a multispot semi‐automated PAttern‐SCAnning Laser (PASCAL) in one session (SS‐PRP) versus four monthly sessions (MS‐PRP) in diabetic retinopathy.MethodsMulticentre, prospective, randomized, single‐blinded, controlled trial evaluating the noninferiority of SS‐PRP versus MS‐PRP for CRT measured with macular spectral‐domain optical coherence tomography (SD‐OCT), with a 9‐month follow‐up in patients presenting severe non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The Manchester study found a significant increase in central subfield retinal thickness after PRP through follow-up [16]. Gabrielle et al found that central subfield retinal thickness increased slightly with time effect during the follow-up [17]. In this study, we also found a slight increase in retinal thickness at the macular grid in eyes with PRP compared to eyes without PRP.…”
Section: Discussionsupporting
confidence: 72%
“…The Manchester study found a significant increase in central subfield retinal thickness after PRP through follow-up [16]. Gabrielle et al found that central subfield retinal thickness increased slightly with time effect during the follow-up [17]. In this study, we also found a slight increase in retinal thickness at the macular grid in eyes with PRP compared to eyes without PRP.…”
Section: Discussionsupporting
confidence: 72%
“…Although intravitreal injection of anti-VEGF agents has been the standard therapy for DME, LP treatment is still often used ( 2 ). LP therapy is associated with severe vision loss ( 36 ). With the development of novel LP technologies, these adverse effects have reduced ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study found no significant difference in CMT between conventional and PASCAL PRP. 10 However, it only examined patients without macular edema at baseline. While this provides valuable data on the rate and magnitude of macular edema formation after PRP, from these data we cannot assess the effect PRP may have on existing macular edema and is not generalizable to patients with macular edema, which is common in PDR.…”
Section: Discussionmentioning
confidence: 99%